Empon Empon Herbal Intake and Increased Breast Milk Production: Konsumsi Jamu Empon-Empon dan Peningkatan Produksi ASI Postpartum - Sari, Pramudya Novita; Astuti, Dwi; Indrianingrum, Irawati (Academia Open, 2026)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:67cfc11f-356f-4c58-97e9-21d0d64b1e28-0" data-testid="conversation-turn-2" data-scroll-anchor="true" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="c1066637-c4d7-4fbc-895f-cc07f99b6440" data-turn-start-message="true" data-message-model-slug="gpt-5-3"> General Background: Breast milk production during the postpartum period is a critical factor in successful breastfeeding, yet many mothers experience challenges in achieving adequate lactation. Specific Background: Traditional herbal practices such as empon-empon consumption are widely used in Indonesian communities as part of postpartum care, believed to support lactation through bioactive compounds. Knowledge Gap: Previous studies have primarily examined general herbal benefits, with limited contextual evidence on the relationship between empon-empon consumption and breast milk production within independent midwifery practices. Aims: This study aims to analyze changes in breast milk production before and after consuming empon-empon herbal drink among postpartum mothers at PMB Dwi Ningrum, Demak. Results: Using a quasi-experimental one-group pretest–posttest design involving 79 respondents, findings showed an increase in the proportion of mothers with smooth breast milk production from 24.1% before intervention to 60.8% after consumption, with statistically significant differences based on the Wilcoxon test. Novelty: This study provides empirical, context-specific evidence integrating local cultural practices and lactation outcomes within community-based midwifery services. Implications: The findings suggest that empon-empon herbal consumption can be considered as a complementary approach to support lactation, while emphasizing the importance of comprehensive breastfeeding management, including maternal nutrition, psychological condition, and family support. Highlights • Breast milk flow increased substantially after herbal consumption period • Significant statistical difference observed between pretest and posttest conditions • Community-based traditional practices documented within midwifery service context Keywords Postpartum Period; Empon-Empon Herbal Drink; Breast Milk Production; Postpartum Mothers; Pretest Posttest Design